HIV, Tuberculosis, and Otogenic Intracranial Sepsis: A Devastating Disease With a Subtle Presentation. Issue 7 (August 2019) - Yakobi, Akhona; Porterfield, James Zachary; Toman, Julia; Spock, Todd; Kapil, Narain; de Meyer, Jenine; Kejner, Alex; Rea, Peter; Gleeson, Michael; Enicker, Basil; Michaelides, Elias; Saman, Yougan
Abstract : Objectives: To undertake a large-scale review of otogenic intracranial sepsis in an area of highly prevalent HIV and tuberculosis (TB) to re-examine and inform early diagnosis and treatment efforts. Methods: Seventy-seven consecutive cases of otogenic intracranial sepsis in KwaZulu-Natal, South Africa were reviewed for demographics, presentation, imaging, HIV status, culture results, and outcomes. Results: The most common intracranial complications were intracranial abscess (46.8%), hydrocephalus (31.2%), subdural empyema (28.6%), and epidural empyema (26.0%). Ear discharge (87.0%), postauricular abscess (29.9%), and hearing loss (29.9%) were notable presenting symptoms. Overall mortality was 15.6%. Of the 45.5% of patients with HIV testing, 54.2% were HIV+, Mortality among HIV+ patients was 15.8% but only 6.3% in HIV− patients ( p  = 0.61, OR = 2.8). Eight patients (10.4%) had culture or histological evidence of TB infection. Conclusions: Otogenic intracranial complications continue to present late and are associated with significant mortality and morbidity, despite advances in diagnostic and treatment modalities. This study represents one of the largest case-series in the literature, and the first to specifically evaluate the effects of HIV and TB infection. Patient presentation and severity of illness varied; however, a majority of patients presented with ear discharge and no focal neurological signs. An effect size for higher mortality among HIV+ patients compared with HIV− patients was noted but was not significant. Tuberculosis infection was prevalent compared with previous studies. This study reinforces the need for enhanced screening and early treatment of ear disease to minimize associated mortality and morbidity, particularly in immunocompromised patients.